HUBUNGAN PEMBELAJARAN DARING TERHADAP KECEMASAN PADA MAHASISWA TINGKAT AKHIR DI MASA PANDEMI COVID-19 - Jessisca, Inggit; Sriningsih, Nining (Nusantara Hasana Berdikari, 2021)
Online lectures or commonly referred to as online are a form of using the internet that can increase the role of students in the learning process. The term online is an acronym for